An update on imatinib mesylate therapy in chronic myeloid leukaemia patients in a teaching hospital in Malaysia - Bee, P.C.; Gan, G.G.; Tai, Y.T.; Haris, A.R.; Chin, E.; Veera, S.N. (2012)
INTRODUCTION: The introduction of imatinib mesylate in 1998 has changed the management of chronic myeloid leukaemia. It is now the first-line therapy for newly diagnosed chronic myeloid leukaemia patients worldwide. However, its long-term survival benefit still needs to be established in clinical setting among Asian patients. METHODS: All chronic myeloid leukaemia patients in the chronic phase who were on imatinib mesylate therapy were retrospectively reviewed. Data was collected through a review of case notes, which was then processed, managed and analysed. RESULTS: A total of 44 patients were included in the study. The cumulative rates of complete haematological response, major cytogenetic response and major molecular response were 93.2%, 75.0% and 34.2%, respectively. The overall survival and event-free survival at five years were 86.0% and 84.9%, respectively. 31.8% of the patients developed anaemia, 29.5% neutropenia and 27.3% thrombocytopenia. A total of 43.2% of patients developed non-haematological side effects. Higher dosage (> 600 mg) and smaller body size (< 60 kg) were risk factors for haematological side effects. Patients with major cytogenetic response and absence of thrombocytopenia had better survival. CONCLUSION: The majority of our chronic myeloid leukaemia patients did well with imatinib therapy. The adverse effects in our patients were tolerable, and no patient had to stop treatment permanently.